Ternary Solid Dispersion Improves Anti-cancer Activity of Alpha-mangostin Against MCF-7 Breast Cancer Cells - Budiman, Arif; Yunita, Ellen Nathania; Rusdin, Agus; Marcelino, Jeremy; Amaliah, Salma; Aulifa, Diah Lia (The Prodia Education and Research Institute (PERI), 2026)
BACKGROUND: Alpha-mangostin (AM) exhibits potent anti-breast cancer activity but its therapeutic effectiveness is constrained due to low aqueous solubility and poor bioavailability. Ternary solid dispersions (TSDs) were developed by adding another excipient to address these challenges. Nevertheless, limited studies have systematically evaluated whether improvements in dissolution and stability achieved through TSD systems are translated into enhanced in vitro cytotoxicity of AM. Therefore, TSD system of AM with Eudragit (EUD) and Poloxamer (POL) was developed, and in vitro cytotoxicity activity was evaluated as a preliminary proof-of-concept in MCF-7 breast cancer cells.METHODS: TSD of AM was prepared by solvent evaporation and characterized by Power X-Ray Diffraction (PXRD), Differential Scanning Calorimetry (DSC), and Fourier Transform Infrared (FT-IR) Spectroscopy. The pharmaceutical properties were evaluated by in vitro dissolution test using a standard paddle apparatus, while physical stability was assessed under two relative humidity environments. The in vitro anticancer efficacy was examined in MCF-7 breast cancer cell using an MTT assay.RESULTS: Amorphization of TSD was confirmed by a halo pattern with PXRD measurements and the absence of an AM melting peak in the DSC curve. FT-IR analysis revealed hydrogen bond interactions between the carbonyl group of AM and EUD/POL protons. TSD system significantly improved the dissolution profile and enhanced cytotoxic effects, reducing cell viability to 1.17% at 16 µg/mL with an IC50 of 7.11 μg/mL (CI 95%: 6.626-7.591).CONCLUSION: The TSD system significantly improved dissolution profile and in vitro cytotoxicity in MCF-7 breast cancer cells, providing proof-of-concept for enhancing the biological performance of AM. KEYWORDS: alpha-mangostin, ternary solid dispersions, dissolution, MCF-7, cytotoxicity